Measures and effect in preventing and controlling COVID-19 in Shenzhen - Shuyan Jin; Jing Zheng (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Since December 2019, COVID-19 is still in the global trend of pandemic, prevention and control situation is grim. Shenzhen is adjacent to Hong Kong, with a small area (1997 square kilometers), a large population (23 million people), many ports, immigrant cities and other factors, which have increased the difficulty of preventing and controlling the epidemic situation in Shenzhen. In such a complex situation,